From guidelines to bedside - insomnia treatment practices in South Korea: a nationwide cohort study - Moon, Daa Un; Piao, Zhaoyan; Lee, Do Hyun; Han, Euna (Frontiers in Psychiatry, 2024)
Background: Insomnia is a prevalent disorder that impacts quality of life and leads to significant economic costs. Treatment includes both non-medication and pharmacological interventions, with international guidelines recommending cognitive behavioral therapy for insomnia (CBT-I) as the first-line treatment.Objective: To describe current insomnia treatment practices in South Korea, focusing on pharmacological and non-medication treatments, and to identify gaps in guideline implementation.: This cohort study used data from the Korea National Health Insurance Service-National Sample Cohort (NHIS-NSC) from 2002 to 2019 and identified 18,003 patients newly diagnosed with insomnia between 2015 and 2019. This study analyzed treatment patterns and utilization rates. Results: Of the 18,003 patients, 16,181 (89.9%) received pharmacological treatment, resulting in 35,638 prescriptions. Zolpidem (60%) and benzodiazepines (30-40%) were the most prescribed medications. Most patients were treated in clinics, with consistent dosages and increasing treatment lengths. Psychotherapy claims rose from 3.20% in 2015 to 9.14% in 2019, particularly in general hospitals (22.06% to 48.37%), but remained low in clinics (1.26% to 2.08%). Conclusion: Pharmacological treatments dominate insomnia management in South Korea, with CBT-I being underutilized. Future efforts should focus on integrating nonpharmacological treatment into routine practice and exploring treatment risks and effectiveness based on patient demographics.